2012
DOI: 10.1063/1.4737928
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic Monte Carlo simulations of anisotropic colloids

Abstract: We put forward a simple procedure for extracting dynamical information from Monte Carlo simulations, by appropriate matching of the short-time diffusion tensor with its infinite-dilution limit counterpart, which is supposed to be known. This approach -discarding hydrodynamics interactionsfirst allows us to improve the efficiency of previous Dynamic Monte Carlo algorithms for spherical Brownian particles. In a second step, we address the case of anisotropic colloids with orientational degrees of freedom. As an … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
19
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 23 publications
(22 citation statements)
references
References 28 publications
3
19
0
Order By: Relevance
“…This tendency is the result of a non-monotonic behavior of the main contributions, D + and D − ⊥ , to the total diffusivity, while the minor contributions, D + ⊥ and D − , only decrease with increasing η. This behavior, specially clear in the case of oblate particles, had been reported before by de Miguel and co-workers for prolate particles with smaller anisotropy than that studied here 23 , and by Jabbari-Farouji for infinitely thin disks 24 .…”
Section: Resultssupporting
confidence: 87%
See 2 more Smart Citations
“…This tendency is the result of a non-monotonic behavior of the main contributions, D + and D − ⊥ , to the total diffusivity, while the minor contributions, D + ⊥ and D − , only decrease with increasing η. This behavior, specially clear in the case of oblate particles, had been reported before by de Miguel and co-workers for prolate particles with smaller anisotropy than that studied here 23 , and by Jabbari-Farouji for infinitely thin disks 24 .…”
Section: Resultssupporting
confidence: 87%
“…In summary, we have investigated the dynamics in nematic liquid crystal phases of anisotropic particles, here modelled as oblate and prolate spherocylinders that confirm previous results 23, 24 and enrich the global picture of transport of particles in the nematic phase. In particular, our comparative study unveils that the generally accepted ability of prolate particles to diffuse faster than their oblate counterparts strongly depends on how this comparison is practically operated.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…We further investigated the dynamics of the orientationally disordered structures with vanishing S = 0 by means of dynamic Monte-Carlo (DMC) that we have developed for anisotropic colloids [35]. In this case, very small values of displacements were used and we performed 0.1 − 2 × 10 7 MC cycles to obtain the dynamical quantities.…”
Section: Simulation Methods and Detailsmentioning
confidence: 99%
“…It was found that Monte Carlo simulations in which physically relevant moves (small particle displacements) are used, are a correct and efficient way to investigate the dynamics in colloidal systems. [43][44][45] Molecular dynamics simulations are less appropriate to describe the dynamics in suspensions of colloidal particles, as they employ Newtonian dynamics rather than the Brownian dynamics which is operative in colloidal systems. We expect only limited fractionation, to the extent introduced by the selected initial configuration and allowed for by the diffusion of the particles on simulation timescales.…”
Section: Introductionmentioning
confidence: 99%